Carbon Dots‐Regulated Pomegranate‐Like Metal Oxide Composites: From Growth Mechanism to Lithium Storage. Issue 6 (23rd April 2022) - Ye, Yu; Wang, Haoji; Liu, Huaxin; Xiang, Yinger; Liu, Lu; Deng, Wentao; Zou, Guoqiang; Liu, Youcai; Hou, Hongshuai; Ji, Xiaobo
Abstract: Carbon dots (CDs) are considered as excellent structural regulator for metal oxides (MOs) due to their abundant functional groups, superior dispersibility, and ultrasmall size (< 10 nm). Herein, a new approach is proposed to construct porous pomegranate‐like MOs/CDs composite based on the CDs‐induced in situ growth mechanism of ion adsorption–multipoint surface nucleation–crosslinking agglomeration. The proposed methodology is successfully applied to prepare SnO2 /CDs, Cu2 O/CDs, and Fe2 O3 /CDs composites, respectively, demonstrating its universality to metal oxides. Taking SnO2 /CDs composite as a case study for anode material in lithium‐ion batteries, it exhibits high lithium storage capacity, excellent cycling stability, and a special feature of capacity increase upon cycling. This study provides a new idea for the design of metal oxides materials tuned by CDs and broadens the application of CDs in the field of material synthesis. Abstract : A series of porous pomegranate‐like metal oxide‐carbon dots (M x O y /CDs) composites are designed directionally through the CDs‐induced in situ growth mechanism of metal oxides, further confirming the universality of the mechanism for all metal oxides. Among them, SnO2 /CDs composites exhibit excellent performance in lithium‐ion batteries, heralding further expansion of applications for CDs.